اتجاهات المدرّسين نحو استخدام استراتيجية التعلم التعاوني في التدريس "دراسة ميدانية في مدارس التعليم الثانوي بمحافظة اللاذقية" - حسن, علي; ونوس, ياسمين (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى التعرف على اتجاهات المدرّسين نحو استخدام استراتيجية التعلم التعاوني في التدريس. ولتحقيق أغراض البحث قامت الباحثة بتصميم أداة الدراسة (استبانة) وتطبيقها على عينة مختارة عشوائياً مؤلفة من /200/ مدرّس, وانتهى البحث إلى النتائج التالية: 1- إن استخدام استراتيجية التعلم التعاوني يسهم في تشجيع التعاون والتفاعل بين الطلاب. 2- لايوجد فرق ذو دلالة إحصائية بين المدرّسين في استخدام استراتيجية التعلم التعاوني تبعاً لمتغير الجنس. 3- لايوجد فرق ذو دلالة إحصائية بين المدرّسين في استخدام استراتيجية التعلم التعاوني تبعاً لمتغير الاختصاص. 4- توجد فروق ذات دلالة إحصائية بين المدرّسين في استخدام استراتيجية التعلم التعاوني تبعاً لمتغير الخبرة وهذه الفروق تعود لسنوات الخبرة المتقدمة. This research aims at knowing the attitudes of teachers towards cooperative learning strategies in teaching . To achieve the objectives of the study, the researcher designed the tool of the study ( A Questionnaire ) and applied it on a randomly chosen sample , which consisted of (200) teachers from secondary schools. The results were : 1- Using cooperative learning strategies encourages cooperation and interaction among students . 2- There is no significant statistical differences between teachers in using cooperative learning strategies due to the sex variable . 3- There is no significant statistical difference between teachers in using cooperative learning strategies due to the specialization variable . 4- There are significant statistical differences between teachers in using cooperative learning strategies, due to the experience variable, and those differences are due to the previous years of experience .